Ritual Penjamasan Pusaka - Kamal, Moh. Zainol; Effendi, Ahmad (Proceedings of Annual Conference for Muslim Scholars, 2024)
Ritual Penjamasan Pusaka in Aeng Tong Tong, Saronggi, Sumenep, is a tradition that combines Islamic values with local wisdom. This sacred ceremony not only preserves cultural heritage but also facilitates the blending of Islamic teachings with Madurese culture. During the ritual, sacred heirlooms, especially Keris, are symbolically purified through spiritually and religiously meaningful processes. Islamic values are reflected in the prayers and efforts to maintain harmony with the Creator, while local wisdom is seen in symbols and customs passed down through generations. This study explores how Islamic and local traditions have blended and examines the social and cultural roles of this ritual in the Aeng Tong Tong community. This research used a qualitative approach, data were collected through observation, interviews, and documentation. The findings show that this ritual strengthens local cultural identity and promotes community cohesion amid changing times.